Gonad Development and Reproductive Ability of Aneuploid Ornamental Koi Carp Obtained by Crossing Triploid Females with Diploid Males. (23rd April 2019) - Gomelsky, Boris; Warner, Jeffrey L.; Delomas, Thomas A.; Novelo, Noel D.; Kramer, Alexander G.
Abstract: It was described earlier that triploid female koi (ornamental variant of the Common Carp Cyprinus carpio ) from heat‐shocked progeny developed large ovaries and produced mass aneuploid progeny when crossed with normal diploid koi males. This study presents data on gonad development and reproductive ability of aneuploid koi obtained from triploid females. Aneuploid koi had low viability when raised in indoor recirculating systems; only 12–19% of fish survived up to 25–28 months of age. The 28‐month‐old aneuploid fish with a ploidy range of 2.31–2.78n obtained in 2013 ( n = 30) did not release sperm or eggs after hormonal injection. Dissection of fish showed that similar to triploid males, aneuploid males had pinkish testes that did not contain sperm; the gonadosomatic index (GSI) of aneuploid males varied from 0.3% to 3.5%, with a mean value of 1.2%. More than 50% of aneuploid females had ovaries that were severely reduced in development, with GSI values less than 2%; about 40% of females had ovaries at the maturing stage, with GSIs ranging from 2.5% to 5.6%. One aneuploid female had mature ovaries filled with fully grown oocytes (GSI = 9.6%). The aneuploid fish obtained in 2015 ( n = 165) did not produce sperm at 25 months of age; all fish from this group died during subsequent overwintering in an earthen pond. Our results show that aneuploid koi males are functionally sterile, whereas some potentially fertile aneuploid females can be found. However, because aneuploid koi have very low viability, the chance of survival for fertile aneuploid females is low, especially under natural conditions. Fertile aneuploid females, even if they survive, would likely produce aneuploid eggs, and fertilization of those eggs would again result in aneuploid progeny with low viability and fertility.